170k views
3 votes
Rewrite f(x) = 2(x − 1)2 + 3 from vertex form to standard form.

f(x) = 2x2 + 5
f(x) = 4x2 − 8x + 7
f(x) = 2x2 + 4x + 5
f(x) = 2x2 − 4x + 5

2 Answers

5 votes
He knew what he was doing.
User Cahit Gungor
by
5.3k points
4 votes

Answer:

Explanation:

f(x) = 2(x − 1)² + 3

= 2 ( x² - 2x +1) +3

= 2x² - 4x +2 +3

f(x) = 2x² − 4x + 5 .....standard form.

User Qasim Ali
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.